Az autonóm helyi jogalkotás korlátai : Esettanulmány a Fővárosi Önkormányzat jogalkotási gyakorlatából (Limitations of autonomous municipal legislation : A case study of the legislative practice of the Municipality of Budapest) - Kristóf Balázs Cseh (KözigazgatásTudomány)
More and more aspects of local government autonomy have been challenged in the recent years. For local authorities, which are redefining their tasks, legislative capacity is of paramount importance, especially the original legislative powers to create new legal instruments to meet the requirements of the 21st century. One of the areas in which local government is working is the development of new mechanisms for public involvement and the creation of new legal instruments to facilitate participation. However, legislation to this end is often difficult in the current legal environment. This paper illustrates the challenges faced by local legislators when trying to develop new instruments for public participation through the creation of a participatory instrument by the Municipality of Budapest. To this end, after a brief introduction to the legislative context of local legislation and the instruments of local participatory democracy, it traces the codification process, presents the resulting legal instrument and explores the dilemmas that arose during the process of public consultation, impact assessment and the incorporation of the codification into the legal environment, as presented in the legislation.